2020
DOI: 10.3390/ijms21165775
|View full text |Cite
|
Sign up to set email alerts
|

The Remedial Potential of Lycopene in Pancreatitis through Regulation of Autophagy

Abstract: Autophagy is an evolutionarily conserved process that degrades damaged organelles and recycles macromolecules to support cell survival. However, in certain disease states, dysregulated autophagy can play an important role in cell death. In pancreatitis, the accumulation of autophagic vacuoles and damaged mitochondria and premature activation of trypsinogen are shown in pancreatic acinar cells (PACs), which are the hallmarks of impaired autophagy. Oxidative stress mediates inflammatory signaling and cytokine ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 112 publications
1
15
0
1
Order By: Relevance
“…Subsequently, the results suggested that the application of Angelicaoneu powders significantly reduced the inflammatory response, while the cell survival rate decreased and the apoptosis rate increased. The low expression of P62 and high expression of LC3-II confirmed that Angelicaoneu powders promoted autophagy to regulate the inflammatory response, while the increased AMPK and SIRT1 indicated that they were related to autophagy (24). Lycopene can improve pancreatitis by preventing oxidative stress-induced autophagy injury and/or directly activating autophagy in pancreatic acinocytes (25).…”
Section: Discussionmentioning
confidence: 90%
“…Subsequently, the results suggested that the application of Angelicaoneu powders significantly reduced the inflammatory response, while the cell survival rate decreased and the apoptosis rate increased. The low expression of P62 and high expression of LC3-II confirmed that Angelicaoneu powders promoted autophagy to regulate the inflammatory response, while the increased AMPK and SIRT1 indicated that they were related to autophagy (24). Lycopene can improve pancreatitis by preventing oxidative stress-induced autophagy injury and/or directly activating autophagy in pancreatic acinocytes (25).…”
Section: Discussionmentioning
confidence: 90%
“…Surprisingly, lycopene is the most prevalent carotenoid in the human diet [ 63 ]. Choi and Kim [ 64 ] recently published a review on the relevance of lycopene in pancreatitis, in which they concluded that lycopene, due to its antioxidative properties, could attenuate the severity of pancreatitis by preventing excess ROS-induced autophagy. Their conclusions were based on several papers, in which, for example, lycopene was reported to attenuate cadmium-induced activation of autophagy in murine hippocampal cells [ 52 ], rescue endothelial progenitor cells of type 2 diabetes mellitus (T2DM) rats from excess autophagy [ 53 ], and alleviate gentamicin-mediated cell death, apoptosis, and autophagy [ 54 ].…”
Section: Modulation Of Autophagy By Nutraceuticals: Support For the T...mentioning
confidence: 99%
“…Cho et al [ 68 ], in their review, listed carotenoids that are potentially relevant in ND therapy. Based on their paper, it seems that crocin [ 50 ], lutein [ 57 , 58 , 59 ], lycopene [ 52 , 54 , 64 ], astaxanthin [ 56 , 65 ], and fucoxanthin [ 61 ] could modulate autophagy under specific conditions, although the precise molecular mechanism of the autophagy-modulating activity of carotenoids remains unclear.…”
Section: Modulation Of Autophagy By Nutraceuticals: Support For the T...mentioning
confidence: 99%
“…There was also decreased lipid peroxidation and oxidative stress overall. Numerous animal models have shown the benefits of antioxidant treatment on AP with a reduction in oxidative stress and inflammatory cytokines [46][47][48][49].…”
Section: Roles Of Antioxidant Therapy In Pancreatitis 41 Pharmacological Interventionmentioning
confidence: 99%